1963
DOI: 10.1111/j.1365-3180.1963.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS AFFECTING THE SELECTIVITY OF 2,3‐DICHLOROALLYLDIISOPROPYLTHIOLCARBAMATE (DI‐ALLATE) AGAINST AVENA SPP. IN WHEAT AND BARLEY

Abstract: A series of pot experiments has been undertaken to assess the selectivity of 2,3-dichloroallyldiisopropylthiolcarbamate (di-allate) against Avena spp. in wheat and barley. It is shown that depth of incorporation, depth of sowing, variety and temperature can all influence the degree of selectivity. When di-allate is incorporated deeply before sowing, there is good selectivity against Avenafatua L. (wild oat) in barley, but the order can be influenced by the depth at germination of both crop and weed, since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

1965
1965
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 5 publications
2
28
1
2
Order By: Relevance
“…A la dose de 1,4 kg/ha par exemple, la levee est reduite de 22% par rapport au temoin non traite, tandis que I'allongement de la coleoptile est reduit de 88% (moyenne pour les trois sols ctudies). Cette observation est a rapprocher des etudes realisees sur des herbicides voisins, le di-allate et l'EPTC, montrant que les graines de graminees n'absorbent pas ces herbicides, que les racines en absorbent relativement peu et que la coleoptile est le site principal de l'absorption et de Faction letale (Appleby & Furtick, 1962;Dawson, 1963;Parker, 1963).…”
Section: Sensibilite De Diverses Especes Au Pebc {Essai 1)unclassified
See 1 more Smart Citation
“…A la dose de 1,4 kg/ha par exemple, la levee est reduite de 22% par rapport au temoin non traite, tandis que I'allongement de la coleoptile est reduit de 88% (moyenne pour les trois sols ctudies). Cette observation est a rapprocher des etudes realisees sur des herbicides voisins, le di-allate et l'EPTC, montrant que les graines de graminees n'absorbent pas ces herbicides, que les racines en absorbent relativement peu et que la coleoptile est le site principal de l'absorption et de Faction letale (Appleby & Furtick, 1962;Dawson, 1963;Parker, 1963).…”
Section: Sensibilite De Diverses Especes Au Pebc {Essai 1)unclassified
“…L'incorporation profonde a tres nettement reduit l'activite herbicide du PEBC, sans doute en diluant l'herbicide dans une couche de terre plus epaisse. Le PEBC, comme d'autres carbamates \'oisins tels que l'EPTC ou le di-allate, est probablement absorbe par la tige des plantes au moins autant, sinon plus, que par les racines (Appleby & Furtick, 1962;Parker, 1963), et peut-etre aussi a l 'etat de vapeur {Yamaguchi, 1961). L'enfouissement du produit dans le sol a proximite des racines ne peut, dans ce cas, augmenter son activite, et l'incorporation ne pourrait etre justifiee que pour soustraire l'herbicide aux faeteurs de degradation.…”
Section: Essai-pre-emergence Sur Betteraves Fourrageresunclassified
“…Friesen, • Present address: School of Biological and Environmental Studies, The New University of Ulster, Coleraine, Co. Londonderry, N. Ireland. Banting & Walker (1962) showed that grass species differed in their sensitivity to localized placement of 5'-(2,3-dichloroallyl)-jVjV-di-isopropylthiolcarbamate (di-allate) in the shoot zone, while Parker (1963) demonstrated that in Avena spp. the base of the coleoptile was the most sensitive zone to di-allate.…”
Section: Introductionmentioning
confidence: 99%
“…Spring wheat (Triticum aestivum L.) is less susceptible to injury from di-allate or tri-allate than oats but wheat can be seriously damaged if sown in treated soil. Injury to wheat can be avoided or reduced, however, if the seeds are planted 1 -3 cm or more below a layer of treated soil, at rates lethal to Avena fatua (Friesen gi a/., 1962;Parker, 1963). These differences have been explained on the basis that in wheat the stem apex is moved into the treated layer of soil at a later stage than in A. fatua (Parker, 1963).…”
Section: Introductionmentioning
confidence: 99%